2022
DOI: 10.3390/medicina58121783
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management during Extracorporeal Membrane Oxygenation—A Mini-Review

Abstract: Extracorporeal membrane oxygenation (ECMO) has been established as a life-saving technique for patients with the most severe forms of respiratory or cardiac failure. It can, however, be associated with severe complications. Anticoagulation therapy is required to prevent ECMO circuit thrombosis. It is, however, associated with an increased risk of hemocoagulation disorders. Thus, safe anticoagulation is a cornerstone of ECMO therapy. The most frequently used anticoagulant is unfractionated heparin, which can, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…10,43,44 However, UFH is the preferred anticoagulant of choice for patients undergoing cardiac surgery, patients supported by ECMO, and critically unwell patients in the intensive care units requiring anticoagulation due to shorter half-life, independence from renal function, and reversibility by protamine sulfate. 10,45,46 Several large studies demonstrated that there were no significant differences in the safety and efficacy of LMWH compared to UFH in treatment of venous thromboembolism. 47,48 Two meta-analyses reported that LMWHs are safer and more effective than UFH.…”
Section: Unfractionated Heparin Versus Low Molecular Weight Heparinmentioning
confidence: 99%
See 1 more Smart Citation
“…10,43,44 However, UFH is the preferred anticoagulant of choice for patients undergoing cardiac surgery, patients supported by ECMO, and critically unwell patients in the intensive care units requiring anticoagulation due to shorter half-life, independence from renal function, and reversibility by protamine sulfate. 10,45,46 Several large studies demonstrated that there were no significant differences in the safety and efficacy of LMWH compared to UFH in treatment of venous thromboembolism. 47,48 Two meta-analyses reported that LMWHs are safer and more effective than UFH.…”
Section: Unfractionated Heparin Versus Low Molecular Weight Heparinmentioning
confidence: 99%
“…10 43 44 However, UFH is the preferred anticoagulant of choice for patients undergoing cardiac surgery, patients supported by ECMO, and critically unwell patients in the intensive care units requiring anticoagulation due to shorter half-life, independence from renal function, and reversibility by protamine sulfate. 10 45 46…”
Section: Unfractionated Heparin Versus Low Molecular Weight Heparinmentioning
confidence: 99%
“…According to the current literature, several pharmacological agents can be used as anticoagulants in patients with ECMO. These are: unfractionated heparin (UFH), low-molecular-weight heparin (LMWH), fondaparinux, and direct thrombin inhibitors [ 11 , 12 ]. Nevertheless, more than choosing the right agent, another challenge is finding and deciding on the appropriate target and the most suitable testing method.…”
Section: Ecmo Circuit Interactions With Coagulation Systemmentioning
confidence: 99%